Analisis Preferensi Mall Culture Dalam Gaya Hidup Konsumtif - Vionata Gadis Ranika; Ainul Mutrofin; Elanda Cika Alodya Nathania (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research is entitled "Analysis of Mall Culture Preferences in the Consumption Lifestyle of Students", based on several factors that cause students to choose shopping centers or malls as a place to visit frequently. The purpose of this study is to find out how many students have high consumerism. Using qualitative research methods through a phenomenological approach, Baudrillard's sign value consumption theory. Consumerism and consumptive lifestyles among students are influenced by various factors, including social pressure, the desire to obtain a social image that wants to be recognized, and the influence of mall culture.